Dynamic but discordant alterations in zDHHC5 expression and palmitoylation of its substrates in cardiac pathologies - Main, Alice; Boguslavskyi, Andri; Howie, Jacqueline; Kuo, Chien-Wen; Rankin, Aileen; Burton, Francis L.; Smith, Godfrey L.; Hajjar, Roger; Baillie, George S.; Campbell, Kenneth S.; Shattock, Michael J.; Fuller, William (Frontiers in Physiology, 2022)
S-palmitoylation is an essential lipid modification catalysed by zDHHC-palmitoyl acyltransferases that regulates the localisation and activity of substrates in every class of protein and tissue investigated to date. In the heart, S-palmitoylation regulates sodium-calcium exchanger (NCX1) inactivation, phospholemman (PLM) inhibition of the Na+/K+ ATPase, Nav1.5 influence on membrane excitability and membrane localisation of heterotrimeric G-proteins. The cell surface localised enzyme zDHHC5 palmitoylates NCX1 and PLM and is implicated in injury during anoxia/reperfusion. Little is known about how palmitoylation remodels in cardiac diseases. We investigated expression of zDHHC5 in animal models of left ventricular hypertrophy (LVH) and heart failure (HF), along with HF tissue from humans. zDHHC5 expression increased rapidly during onset of LVH, whilst HF was associated with decreased zDHHC5 expression. Paradoxically, palmitoylation of the zDHHC5 substrate NCX1 was significantly reduced in LVH but increased in human HF, while palmitoylation of the zDHHC5 substrate PLM was unchanged in all settings. Overexpression of zDHHC5 in rabbit ventricular cardiomyocytes did not alter palmitoylation of its substrates or overall cardiomyocyte contractility, suggesting changes in zDHHC5 expression in disease may not be a primary driver of pathology. zDHHC5 itself is regulated by post-translational modifications, including palmitoylation in its C-terminal tail. We found that in HF palmitoylation of zDHHC5 changed in the same manner as palmitoylation of NCX1, suggesting additional regulatory mechanisms may be involved. This study provides novel evidence that palmitoylation of cardiac substrates is altered in the setting of HF, and that expression of zDHHC5 is dysregulated in both hypertrophy and HF.